2007
DOI: 10.1242/jcs.011163
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial electron-transport-chain inhibitors of complexes I and II induce autophagic cell death mediated by reactive oxygen species

Abstract: Autophagy is a self-digestion process important for cell survival during starvation. It has also been described as a form of programmed cell death. Mitochondria are important regulators of autophagy-induced cell death and damaged mitochondria are often degraded by autophagosomes. Inhibition of the mitochondrial electron transport chain (mETC) induces cell death through generating reactive oxygen species (ROS). The role of mETC inhibitors in autophagy-induced cell death is unknown. Herein, we determined that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
306
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(330 citation statements)
references
References 38 publications
20
306
0
4
Order By: Relevance
“…Our previous studies indicate that mETC inhibitors (including complex I inhibitor rotenone, complex II inhibitor TTFA, and complex I/SOD inhibitor 2-ME 23,28 ) can induce ROSmediated autophagy and autophagic cell death in cancer cells. 17,18 In these studies, SOD2 overexpression reduced autophagy, supporting the involvement of O 2 KÀ in autophagy induction. However, by measuring ROS only with dihydroethidium (DHE), which is reported to detect O 2 KÀ specifically, 27 we failed to directly address the function of H 2 O 2 .…”
Section: Autophagy Induced By Metc Inhibitors Is Mediated By Osupporting
confidence: 59%
See 2 more Smart Citations
“…Our previous studies indicate that mETC inhibitors (including complex I inhibitor rotenone, complex II inhibitor TTFA, and complex I/SOD inhibitor 2-ME 23,28 ) can induce ROSmediated autophagy and autophagic cell death in cancer cells. 17,18 In these studies, SOD2 overexpression reduced autophagy, supporting the involvement of O 2 KÀ in autophagy induction. However, by measuring ROS only with dihydroethidium (DHE), which is reported to detect O 2 KÀ specifically, 27 we failed to directly address the function of H 2 O 2 .…”
Section: Autophagy Induced By Metc Inhibitors Is Mediated By Osupporting
confidence: 59%
“…Several reports have suggested that starvation-induced autophagy is mediated by ROS. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In this study, we investigated the generation of O 2 KÀ and H 2 O 2 under two starvation conditions: starvation of glucose, L-glutamine, pyruvate, and serum (GP), and starvation of amino acids and serum (AA). Cellular levels of O 2 KÀ and H 2 O 2 were measured by flow cytometry using specific fluorescent dyes (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon formation of autophagic vacuoles, cytosolic LC3B (isoform I, LC3B I) is cleaved and inserted into the autopha gic membrane (isoform II, LC3B II), allowing autophagy to be monitored by measuring the LC3B II/LC3B I ratio (Levine and Kroemer, 2008). Previous literature has shown that the mitochondrial toxicant rotenone induces autophagy (Chen et al, 2007). Remarkably, we saw a significant defect in rotenone induced autophagy in CSB deficient CS1AN cells and HSMM after 24 h of treatment (Fig.…”
Section: Csb-deficient Cells Show Decreased Autophagy and An Accumulamentioning
confidence: 55%
“…Recent studies provide strong evidences for the involvement of mitochondrially-generated ROS production in the induction of autophagy (Chen & Gibson, 2008;Chen et al, 2009). Recently, it has been demonstrated that targeting mETC complex I by rotenone, induces autophagic cell death through a ROS-mediated mechanism (Chen et al, 2007).…”
Section: Oxidative Stress and Autophagymentioning
confidence: 99%